Increasing Students’ English Vocabulary Mastery by Using Total Physical Response Method - Zainollah, Zainollah; Rohaniyah, Jaftiyatur; Zubaida, Zubaida (English Teaching Journal : A Journal of English Literature, Language and Education, 2024)
This research aims to describe; (1) how Total Physical Response Method (TPR) can increase students’ English vocabulary mastery? This research uses classroom action research by applying Hopkins model and collaborative patterns. This research was carried out in the fifth grade of MI Nasy'atul Muta'allimin Dungkek Sumenep. The data collection techniques used are interview, test, observation and documentation. Meanwhile, the technique of data analysis used quantitative data analysis to analyze student learning outcomes and qualitative data analysis to analyze student learning process. The criteria of success of this research are 100% of students' scores are increased above criteria after the learning process. The results of data analysis show that: Total Physical response method can improve students' English vocabulary mastery. This can be seen from student learning process and outcomes which are increasing from the start of pre-test to the end of cycle II. The results of increasing students' English vocabulary mastery during pre-test only reached 6.7%, with an average score of 47. Meanwhile in cycle 1 there was an increase in learning outcomes, namely increasing to 93.3% with an average score of 87.6. However, in cycle I there was still 1 student who had a score below the criteria. In the second cycle there was a very significant increase in learning outcomes, namely increasing to 100% with an average score of 95.3. So in the second cycle all students have obtained a complete score above the criteria of success.